Marine diesel engine control to meet emission requirements and maintain maneuverability. (July 2018) - Nielsen, Kræn Vodder; Blanke, Mogens; Eriksson, Lars; Vejlgaard-Laursen, Morten
Abstract: International shipping has been reported to account for 13% of global NO x emissions and 2.1% of global green house gas emissions. Recent restrictions of NO x emissions from marine vessels have led to the development of exhaust gas recirculation (EGR) for large two-stroke diesel engines. Meanwhile, the same engines have been downsized and derated to optimize fuel efficiency. The smaller engines reduce the possible vessel acceleration, and to counteract this, the engine controller must be improved to fully utilize the physical potential of the engine. A fuel index limiter based on air/fuel ratio was recently developed (Turbo, 2016), but as it does not account for EGR, accelerations lead to excessive exhaust smoke formation which could damage the engine when recirculated. This paper presents two methods for extending a fuel index limiter function to EGR engines. The methods are validated through simulations with a mean-value engine model and on a vessel operating at sea. Validation tests compare combinations of the two index limiter methods, using either traditional PI control for the EGR loop or the recently developed fast adaptive feedforward EGR control (Nielsen et al., 2017a). The experiments show that the extended limiters reduce exhaust smoke formation during acceleration to a minimum, and that the suggested limiter, combined with adaptive feedforward EGR control, is able to maintain full engine acceleration capability. Sea tests with engine speed steps from 35 to 50 RPM, made peak exhaust opacity increase by only 5% points when using the proposed limiter, whereas it increased 70% points without the limiter.